Regional economic integration among South East Asian countries - Sen, Raj Kumar 1945-; Bhat, G. M. 1956-; International Institute of Development Studies (Kolkata, India) (New Delhi Published on behalf of the International Institute of Development Studies by Regal Publications, 2014)
Papers presented at the 7th International Seminar of International Institute of Development Studies, held at Srinagar.
Section 1. Look east policy and India -- section 2. SAARC and its role in economic integration -- section 3. WTO and its impacts -- section 4. Indo-Pak economic co-operation and other issues -- section 5. FDI and economic development.
Includes bibliographical references and index.
Keywords: Southeast Asia -- Economic integration -- Congresses; Southeast Asia -- Commercial policy -- Congresses